Chinese Catering in Irkutsk - Dyatlova, Elena (project baikal, 2017)
The phenomenon of public catering is observed from the point of view of interaction of national cultures and development of market economy. The types of ethnic public catering and their characteristic features are defined. Chinese catering in Irkutsk is analyzed. The article demonstrates how authenticity of food, decoration and ambiance depends on social demands, social stratification and the mentality of target audience.